The mystery woman - Quick, Amanda (Quick, Amanda. Ladies of Lantern Street novel., 2013)
Targeted by a disabled former spy for the Crown who wrongly believes she is blackmailing his sister, Beatrice Lockwood offers her assistance in tracking down the real culprit and eventually falls for the spy only to find herself hunted by a mad scientist who would resurrect a dead lover.